Numerical analysis of frost penetration around footings of power mills in subarctic conditions - Edeskär, Tommy; Helander, Anders; Knutsson, Sven (Luleå tekniska universitet, Geoteknologi, 2009)
The potential for establishing wind power farms in the subarctic areas is high due to the combination of large available areas and few conflicting interests. In subarctic climate frost and thaw are major principal design aspects. In foundation work the major impact of frost action is at the outer peripheries of the foundation. Therefore most analysis work and prevention actions such as insulation around the foundation are concentrated to this part of the structure. The gravity foundations of wind power plants are often constructed as a reinforced concrete monolite. In the centre of the footing a steel cage is attached for anchoring the wind mill tower. This steel cage ends close to the sub-grade and can due to considerably higher thermal conductivity, compared to the concrete structure, transport a lot more heat. By FEM analysis, the frost penetration around, and under two typical wind-power foundations have been analyzed for different climate conditions in Sweden. In addition, different soil types have also been used. The result shows that the frost penetration in the centre of the foundation needs to be considered. Further it is shown that it is larger in the centre than compared to the periphery. Godkänd; 2009; Bibliografisk uppgift: USB; 20090814 (svek)